Changes in Trauma-Related Cognitions and Emotions After Eliciting Moral Elevation: Examining the Effects of Viewing Others' Virtuous Behavior on Veterans With PTSD - McGuire, Adam P.; Fagan, Joanna G.; Howard, Binh An N.; Wurm, Annika I.; Szabo, Yvette Z. (Frontiers in Health Services, 2022)
Moral elevation is described as feeling inspired after witnessing someone perform a virtuous act. Past work suggests the features of moral elevation may be contrary to PTSD, yet few studies have directly tested its impact on relevant symptoms. This experimental study assessed changes in trauma-related cognitions and emotions from after a trauma reminder task to after an elevation induction exercise. We hypothesized that higher elevation after the induction exercise would be associated with greater reductions in cognitions and emotions. Veterans with probable PTSD (N = 38) completed measures of trauma-related cognitions and emotions, once after a written trauma narrative exercise (T1) and again after watching two videos designed to elicit elevation (T2). Veterans also completed measures of state elevation after each video. Results suggest veterans experienced small, significant decreases in self-blame (d = 0.36) and negative beliefs about others (d = 0.46), and medium, significant decreases in guilt (d = 0.68), shame (d = 0.60), and negative beliefs about self (d = 0.69) between T1 and T2. As hypothesized, higher elevation was associated with significantly greater reductions in multiple outcomes above and beyond the effects of general positive affect. Specifically, there were medium effects for changes in shame (B = -0.42, SE = 0.17, p = .019, change in f2 = 0.25), negative view of others (B = -0.34, SE = 0.16, p = .044, change in f2 = 0.20), and a large effect for changes in negative view of self (B = -0.31, SE = 0.13, p = .019, change in f2 = 0.54). These findings suggest elevation may be well-suited to target trauma-related symptoms and future research should further examine its clinical utility.